Allelopathic Potential of Lantana camara L. Leaf Extracts and Soils Invaded by It on the Growth Performance of Lepidium sativum L. - Likyelesh Gebreyohannes; Meseret C. Egigu; M. Manikandan; J. M. Sasikumar (The Scientific World Journal)
Lantana camara is a noxious invasive plant that invades agricultural and natural ecosystems. In the current study, phytotoxicity of hexane and ethanolic leaf extracts of L. camara in different concentrations and soils invaded by it on Lepidium sativum were investigated under laboratory conditions. Soil toxicity was evaluated by comparing the growth of L. sativum on soils sampled from Lantana-invaded and Lantana-free sites. Results showed that extract concentrations and solvent type and their interaction significantly reduced percent seed germination and seedling growth. Compared to control (distilled water), both hexane and ethanol extracts at 5% w/v concentration significantly reduced percent germination and early seedling growth and completely inhibited seed germination at 10% w/v of hexane leaf extract, suggesting that hexane extract has a greater inhibitory effect than ethanolic extract in all the parameters measured. However, growth performance and seed yield of L. sativum grown on soil invaded by Lantana did not significantly vary from those grown on soils sampled from noninvaded sites. The results of this study generally showed that though Lantana leaf extracts have a direct negative allelopathic effect on L. sativum, soils invaded by Lantana have no toxic materials in the soil to directly or indirectly inhibit the growth of L. sativum. Further field studies on allelopathic effects of Lantana on L. sativum are recommended.